2018
DOI: 10.12678/1089-313x.22.2.84
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Footwear on Free Moments During a Rotational Movement in Country Swing Dance

Abstract: Footwear in dance has been studied for support and cushioning, but little research has been conducted on free moments, which may result from high frictional coefficients. Conversely, insufficient friction between shoes and floors may increase the risk of falls and compromise dance performance. The purpose of this study was to examine the effect of different types of footwear with different coefficients of friction on peak and average free moments during a rotational movement in country swing dance. Fifteen cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…29,30 While some researchers and industry professionals are interested in developing new pointe shoe designs, 26,27,29 the dance medicine and science community currently lacks necessary understanding of the impacts that specific pointe shoe characteristics may have on dancers' health. Whereas there is a growing body of evidence regarding specifications of jazz 16,31,32 and cultural dance shoes, 17,33 ballet footwear investigations have predominantly focused on balance measures [34][35][36][37][38][39] and plantar pressure concerns [40][41][42] in pointe shoes, without regard to shoe specifics.…”
Section: Ground Reaction Forces In Ballet Differences Resulting From ...mentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 While some researchers and industry professionals are interested in developing new pointe shoe designs, 26,27,29 the dance medicine and science community currently lacks necessary understanding of the impacts that specific pointe shoe characteristics may have on dancers' health. Whereas there is a growing body of evidence regarding specifications of jazz 16,31,32 and cultural dance shoes, 17,33 ballet footwear investigations have predominantly focused on balance measures [34][35][36][37][38][39] and plantar pressure concerns [40][41][42] in pointe shoes, without regard to shoe specifics.…”
Section: Ground Reaction Forces In Ballet Differences Resulting From ...mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] High GRF can have detrimental effects on the body and can result from inadequate dance surfaces, 9,10 poor technique, 11 and the footwear utilized. [12][13][14][15][16][17][18] When landing on nonresilient surfaces, the dancer's body must absorb additional force, potentially increasing risk of injury. 4,9,10,18 While it has been demonstrated that emphasizing proper landing technique can help decrease the effects of GRF on a dancer's body, 19,20 there are many characteristics of ballet footwear that have not yet been fully explored for their possible influence on GRF.…”
mentioning
confidence: 99%